Analisis Faktor Penerimaan Dan Penggunaan Aplikasi Palui Baiman Menggunakan Technology Acceptance Model (TAM) - Husnul Khatimi; Muhammad Alkaff; Muhammad Ridho A.G.D. (ISB Atma Luhur, 2022)
The application of E-Government is a solution about how efforts to increase and benefit are obtained by the community from public services designed by the government under Mayor Regulation Number 41 of 2018 concerning E-Government Implementation utilizing Information Technology by forming an Android-based information system with the name Application Integrated Kelurahan Administration Services or can be called the